Derivation of allometric equations and carbon content estimation in mangrove forests of Malaysia - Khan, Waseem Razzaq; Giani, Michele; Bevilacqua, Stanislao; Anees, Shoaib Ahmad; Mehmood, Kaleem; Nazre, M.; Abdul Haddy, Abdul Aziz; Abang Median, Abang Norizan; Bujang, Japanie Bin; Mohamad-Ismail, Fatin Norliyana; Mohamed, Johar; Samdin, Zaiton; et al. (Elsevier B.V., 2025)
Mangrove forests play a vital role in carbon sequestration and climate change mitigation, yet comprehensive data on their carbon storage capacity in Malaysia remain limited. This study investigated allometric relationships and carbon content in Malaysian mangrove forests, aiming to develop site species-specific allometric equations, determine carbon content in tree components, and assess total carbon stock. Research was conducted in four compartments of the Sg. Pulai Permanent Reserved Forest, representing a mixed-species mangrove stand. We measured 1403 trees across ten species, with Rhizophora apiculata identified as the dominant species. Using diameter at breast height (DBH) and tree height, we developed site species-specific allometric equations to estimate aboveground biomass. The total aboveground biomass ranged from 183.30 t ha⁻1 to 187.06 t ha⁻1 across the study area. We calculated the total carbon stock at 91.01 t C ha⁻1, incorporating measurements from trees below 5 cm in diameter, dead and downed wood, and litter. An economic valuation of carbon storage was conducted using two approaches: the social cost of carbon method estimated a value of USD 4054.76 per hectare. In contrast, the market price approach yielded USD 1064.34 per hectare. This study provides essential data for improving biomass and carbon stock estimation methods in Malaysian mangrove ecosystems. Our findings highlight these forests' economic and ecological importance, supporting their integration into climate change mitigation strategies and informing sustainable management and conservation policies for mangrove forests in Malaysia and similar regions.